2019
DOI: 10.32933/actainnovations.31.4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Viburnum opulus polyphenolic compounds on metabolic activity and migration of HeLa and MCF cells

Abstract: In recent years, research of antitumor activity of natural compounds isolated from plant material has increased. Polyphenols have gained significant attention due to their proapoptotic abilities and their involvement in migration and inhibition of metastasis processes. The anticancer effects of polyphenolic extracts of Viburnum opulus fruit against human breast (MCF-7) and cervical (HeLa) cancer cell lines have been confirmed in this study. It was demonstrated that the tested preparations (methanol – M and ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…To determine the effects of extracts on cellular migration, Oris™ Cell Migration Assays were done according to the manufacturer's protocol with modifications [16]. Briefly, cells were seeded on the 96-well plate with "stopper" barriers that create a central cell-free detection zone for cell migration experiments.…”
Section: Cell Migration Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the effects of extracts on cellular migration, Oris™ Cell Migration Assays were done according to the manufacturer's protocol with modifications [16]. Briefly, cells were seeded on the 96-well plate with "stopper" barriers that create a central cell-free detection zone for cell migration experiments.…”
Section: Cell Migration Assaymentioning
confidence: 99%
“…To evaluate red clover seed sprouts' chemopreventive properties, we treated cells with t-BOOH, which generates oxidative stress under in vitro conditions via production of tertbutoxyl, peroxyl, alkoxyl and methyl radicals catalyzing lipid peroxidation, DNA strand breaks and alteration in intracellular calcium homeostasis [14,16]. As compared to the untreated cells, t-BOOH lowered cells metabolic activity by almost 20%-30% (Table 3).…”
Section: Trifolium Pratense L As a Chemopreventive Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the extracts on cellular migration was evaluated with a modified scratch-wound assay, which is based on measuring the free detection zone: the standardized round-shaped area decreases with cell migration [ 51 ]. Briefly, cells were seeded overnight on 96-well plates with “stopper” barriers that created a central cell-free detection zone for the cell-migration experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore berry-rich diets are considered as effective means in disease prevention and even their treatment. Earlier studies on V. opulus reported its antioxidant activity [ 5 ] and strong radical scavenging capacity, mainly due to a high phenolic concentration [ 10 ], as well as anticancer activity [ 11 , 12 , 13 ]. For instance, Ceylan et al [ 14 ] reported that the extracts of V. opulus fruits exhibit in vitro and in vivo anticancer activity against Ehrlich ascites carcinoma (EAC) bearing mice, and these effects were related to alkaloids, phenolic compounds, flavonoids, and/or their synergistic effects.…”
Section: Introductionmentioning
confidence: 99%